The Economic Impact of Internet Fraud in Nigeria: An Analysis of Cyber Law in The Digital Age - Abubakar Muhammad Jibril (Proceeding International Conference Restructuring and Transforming Law, 2025)
Internet fraud poses a significant economic challenge in Nigeria, exacerbated by gaps in the country's existing cyber laws. This study aims to analyze the economic impact of internet fraud in Nigeria and explore legal reforms by drawing lessons from Indonesia's successful cyber law framework. Employing a normative juridical approach, the research examines existing literature and comparative legal frameworks with a focus on Indonesia's regulatory achievements in combating cybercrime. The findings reveal that inadequate legal standards contribute substantially to the persistence of internet fraud in Nigeria, while Indonesia's robust legal framework has effectively mitigated similar challenges. Based on these insights, the study offers specific recommendations for reforming Nigeria's cyber laws, advocating for the adoption of best practices from Indonesia to enhance legal effectiveness and reduce economic losses caused by internet fraud.